The influence of the ARPD composition on the heat of dissolution in hydrocarbon solvents. Issue 1 (May 2020) - Ibragimova, D; Sharafieva, Z; Sharifullin, A; Chinedu, U; Isakov, D; Kamara, M
Abstract: In this paper, we studied two samples of asphlatene-resin-paraffin deposits of different composition, precipitated during the extraction of hard-to-recover oil and characterized by different melting points. The samples were studied by the thermal analysis method on the MOM (Hungary) Q-1500D derivatograph. The compositions of samples were studied by SARA-analysis by taking into account the methodical recommendations of ASTM D4124-09 and GOST 32269-201. The process of asphlatene-resin-paraffin deposits dissolving in straight-run fractions was studied. Straight-run fractions 80-180°C and 180-350°C were used for heat dissolution experiments. The heat of dissolution of asphlatene-resin-paraffin deposits in fractions was measured on a calorimeter. The graphs that indicate the dependence of the heat of dissolution of asphlatene-resin-paraffin deposits on its concentration in fractions were plotted. The efficiency of the dissolution process was determined.